Impact of sleep deprivation on colon cancer: Unraveling the KynA-P4HA2-HIF-1α axis in tumor lipid metabolism and metastasis - Zuojie Peng; Jia Song; Wenzhong Zhu; Haijun Bao; Yuan Hu; Yongping Shi; Xukai Cheng; Mi Jiang; Feifei Fang; Jinhuang Chen; Xiaogang Shu (Molecular Metabolism)
Objective: There is growing evidence that sleep deprivation promotes cancer progression. In addition, colon cancer patients often experience sleep deprivation due to factors such as cancer pain and side effects of treatment. The occurrence of liver metastases is an important factor in the mortality of colon cancer patients. However, the relationship between sleep deprivation and liver metastases from colon cancer has not been elucidated. Methods: A sleep deprivation liver metastasis model was constructed to evaluate the effect of sleep deprivation on liver metastasis of colon cancer. Subsequently, mice feces were collected for untargeted metabolomics to screen and identify the key mediator, Kynurenic acid (KynA). Furthermore, HILPDA was screened by transcriptomics, and its potential mechanism was explored through ChIP, co-IP, ubiquitination experiments, phenotyping experiments, etc. Results: Sleep deprivation promotes liver metastases in colon cancer. Functionally, sleep deprivation aggravates lipid accumulation and decreases the production of the microbiota metabolite KynA. In contrast, KynA inhibited colon cancer progression in vitro. In vivo, KynA supplementation reversed the promoting effects of sleep deprivation on liver metastases from colon cancer. Mechanistically, KynA downregulates the expression of P4HA2 to promote the ubiquitination and degradation of HIF-1α, which leads to a decrease in the transcription of HILPDA, and ultimately leads to an increase in lipolysis of colon cancer cells. Conclusions: Our findings reveal that sleep deprivation impairs intracellular lipolysis by KynA, leading to lipid droplets accumulation in colon cancer cells. This process ultimately promotes colon cancer liver metastasis. This suggests a promising strategy for colon cancer treatment.